Individual variation in preference behavior in sailfin fish refines the neurotranscriptomic pathway for mate preference - Rebecca L. Young; Sarah M. Price; Molly Schumer; Silu Wang; Molly E. Cummings (Ecology and Evolution)
Abstract Social interactions can drive distinct gene expression profiles which may vary by social context. Here we use female sailfin molly fish (Poecilia latipinna) to identify genomic profiles associated with preference behavior in distinct social contexts: male interactions (mate choice) versus female interactions (shoaling partner preference). We measured the behavior of 15 females interacting in a non‐contact environment with either two males or two females for 30 min followed by whole‐brain transcriptomic profiling by RNA sequencing. We profiled females that exhibited high levels of social affiliation and great variation in preference behavior to identify an order of magnitude more differentially expressed genes associated with behavioral variation than by differences in social context. Using a linear model (limma), we took advantage of the individual variation in preference behavior to identify unique gene sets that exhibited distinct correlational patterns of expression with preference behavior in each social context. By combining limma and weighted gene co‐expression network analyses (WGCNA) approaches we identified a refined set of 401 genes robustly associated with mate preference that is independent of shoaling partner preference or general social affiliation. While our refined gene set confirmed neural plasticity pathways involvement in moderating female preference behavior, we also identified a significant proportion of discovered that our preference‐associated genes were enriched for ‘immune system’ gene ontology categories. We hypothesize that the association between mate preference and transcriptomic immune function is driven by the less well‐known role of these genes in neural plasticity which is likely involved in higher‐order learning and processing during mate choice decisions.